2016
DOI: 10.12965/jer.1630502.251
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 24-week repeated short-time walking based training program on physical fitness of black Cameroonian obese women

Abstract: This study aimed to examine the effects of a training program based on repetition of short-time walk sequences on cardiorespiratory response, physical performance and metabolic parameters in black Cameroonian obese women. One hundred thirty-nine obese women (body mass in-dex [BMI]>30 kg/m2) were divided into three groups: premenopausal (Pre-M; 39.7±7.9 yr; n=48), postmenopausal (Post-M; 55.0±2.5 yr; n=61) and control group (CONT; 48.7±9.4 yr; n=30). Only Pre-M and Post-M completed 24-week repeated short-time w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 29 publications
2
9
1
1
Order By: Relevance
“…Wong et al (2008) argued that it takes more than 3 months to record physical benefits inherent in regular physical and sports activities. Guessogo et al (2016b) assessed the impact of a 24-week training program including 6 min and 2-km walking tests on anthropometric and lipid profiles in a population of obese Cameroonian women; 2 (8.7) 3 (17.6) 5 (12.5) 4 (17.5) 3 (17.6) 7 (17.5) Obesity (type 2) (35-39.9) 1 (4.3) 1 (5.9) 2 (5.0) -1 (5.9) 1 (2.5)…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Wong et al (2008) argued that it takes more than 3 months to record physical benefits inherent in regular physical and sports activities. Guessogo et al (2016b) assessed the impact of a 24-week training program including 6 min and 2-km walking tests on anthropometric and lipid profiles in a population of obese Cameroonian women; 2 (8.7) 3 (17.6) 5 (12.5) 4 (17.5) 3 (17.6) 7 (17.5) Obesity (type 2) (35-39.9) 1 (4.3) 1 (5.9) 2 (5.0) -1 (5.9) 1 (2.5)…”
Section: Discussionmentioning
confidence: 99%
“…This shows that the intensities of the exercises used in the fitness center of this study were low. It is likely the reason why the study of Guessogo et al (2016b) showed significant improvements in body and lipid parameters which were achieved after 24 weeks of a training program including 2 km and 6-min walking tests. Another factor that needs to be taken into consideration is the qualification of the people who conduct the training in these centers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations